ANALYSIS OF LEVEL OF THE RUSSIAN DIGITAL ECONOMY DEVELOPMENT - N. Malyshkin; E. Halimon (Вестник университета)
This study of the Russian digital economy development that is based on the statistical data of macro- and microeconomics for 2008-2017, regulations, orders, instructions, government programs and international organizations is represented. The ve directions of the Russian digital economy development has been analyzed, in particular, some positive trends, problems and recommendations for their solution, prospects for the formation of new industries has been oered, and the degree of information society has been evaluated. Particular attention was given to the current dicult situation with «digital inequality» in the subjects of Russian Federation, which can further inhibit the development of the digital economy of the whole country.